Which traumatic brain injury patients should be treated with anticoagulants and when?. (March 2014) - Raychaudhuri, Ratul; Litofsky, N Scott
<x xml:space="preserve">Abstract</x> Anticoagulation to prevent venous thromboembotic events in head trauma is a controversial intervention. Neurosurgeons have generally been opposed to the idea. We present our view of the safety and efficacy of chemoprophylaxis for patient with traumatic brain injury, as well as our recommendation for such intervention.